Self-Directed Learning of the 7th Graders of SMP Bukit Asam Tanjung Enim - Malinda, Cindy; Petrus, Ismail; Silvhiany, Sary (JETL (Journal of Education, Teaching and Learning), 2024)
Self-directed learning is an important component of the teaching and learning process. This study aimed to find out; (1) What is the level of self-directed learning of students and (2) What is the most dominant dimension of students’ self-directed learning. The quantitative study was used to answer the research objectives. Data were gathered through questionnaires. This study included 46 students from SMP Bukit Asam Tanjung Enim's 7th grade. To analyze the data, SPSS was used. The findings showed that the mean score for students' self-directed learning was 83.73, with a range of scores from 60 to 95. It means that students’ level of self-directed learning was average. Additionally, motivation received the students' highest average marks for self-directed learning. It revealed that motivation dominated all other factors, with self-monitoring, self-confidence, and self-control coming in last. Overall, the findings suggested that students should practice self-directed learning in the early stages of their education.